SUBJECT-MATTER COMPETENCE IN THE FIELD OF PSYCHO-PEDAGOGY OF AGENCY AS A RESOURCE OF MODERNIZING THE CONTENT OF HIGHER PEDAGOGICAL EDUCATION - Halian, Olena; Halian, Ihor; Halian, Andrii (International Journal of Psychosocial Rehabilitation, 2020)
The system of higher pedagogical education currently is in a situation of modernization. A leading factor in reorienting both the process and the content aspects of future teacher training for the implementation of educational goals is changing the views on the competences that a modern student must acquire. Along with this, comprehension of the realities in which a person lives, the transitivity of one’s existence determines the need to anticipate the image of a graduate and the teacher who is capable of fulfilling educational goals, creating an educational environment for actualization of pupils’ personality resources, their orientation towards education throughout their lives. The question is about the formation of “a new generation of educational workers” (Concept development of pedagogical education, 2018) who are aware of their own professional position and the relevance of semantic, a thought-activity approach towards organizing cooperation of all the subjects in the educational process. The above stated corresponds to the generally recognized holistic value attitude towards pupils, orientation to pupil personality in their education, upbringing and development (Bondarevskaja, 2000; Martin, 2018; Pukelis, Smetona, 2012). At the same time, it presupposes taking into account the agency-related, and not only agent, field of personality activity.